KOMPONEN DAN TUJUAN KOMUNIKASI PENDIDIKAN DALAM PERSPEKTIF PENDIDIKAN ISLAM - Andi Abd. Muis; Nur Aliah; Sudirmanto Sudirmanto; Dewi T (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
ABSTRACT Educational communication is an essential element in the success of learning because it functions as a medium for transmitting knowledge, values, and shaping students' character. However, communication barriers between educators and students still occur, causing the learning process to be less than optimal. This study aims to analyze the components and objectives of educational communication in the learning process from the perspective of Islamic education. The study employed a library research method by examining relevant books, journals, and scientific sources, which were then analyzed descriptively. The findings indicate that educational communication consists of communicators, communicants, messages, media, methods, and feedback that interact to support effective learning. The objectives of educational communication include delivering information, enhancing learning motivation, developing skills, shaping attitudes, strengthening educational relationships, and fostering students' character. The novelty of this study lies in the integration of educational communication concepts with the perspective of Islamic education, positioning communication not only as a means of knowledge transfer but also as a medium for moral development. This study contributes as a reference for teachers and lecturers in developing learning processes that are more interactive, humanistic, and character-oriented. Therefore, effective educational communication serves as a fundamental basis for supporting successful learning and sustainable character development among students. ABSTRAK Komunikasi pendidikan merupakan unsur penting dalam keberhasilan pembelajaran karena berfungsi menyampaikan pengetahuan, nilai, dan membentuk karakter peserta didik. Namun, masih terdapat hambatan komunikasi antara pendidik dan peserta didik yang menyebabkan proses pembelajaran belum berjalan secara optimal. Penelitian ini bertujuan menganalisis komponen dan tujuan komunikasi pendidikan dalam proses pembelajaran berdasarkan perspektif pendidikan Islam. Penelitian menggunakan metode studi kepustakaan (library research) dengan mengkaji berbagai buku, jurnal, dan sumber ilmiah yang relevan, kemudian dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa komunikasi pendidikan mencakup komunikator, komunikan, pesan, media, metode, dan umpan balik yang saling mendukung terciptanya pembelajaran yang efektif. Tujuan komunikasi pendidikan meliputi penyampaian informasi, peningkatan motivasi belajar, pengembangan keterampilan, pembentukan sikap, penguatan hubungan edukatif, dan pembentukan karakter peserta didik. Kebaruan penelitian ini terletak pada integrasi konsep komunikasi pendidikan dengan perspektif pendidikan Islam yang menempatkan komunikasi sebagai sarana transfer pengetahuan sekaligus pembinaan akhlak. Penelitian ini berkontribusi sebagai rujukan bagi guru dan dosen dalam mengembangkan pembelajaran yang lebih interaktif, humanis, dan berorientasi pada karakter. Dengan demikian, komunikasi pendidikan yang efektif menjadi fondasi penting dalam mendukung keberhasilan pembelajaran dan pengembangan karakter peserta didik.